A Comparison of Radiologists' and Urologists' Opinions Regarding Prostate MRI Reporting: Results From a Survey of Specialty Societies - Spilseth, Benjamin; Ghai, Sangeet; Patel, Nayana U.; Taneja, Samir S.; Margolis, Daniel J.; Rosenkrantz, Andrew B. (American journal of roentgenology (1976), 2018)
The purpose of this study is to compare radiologists' and urologists' opinions regarding prostate MRI reporting. Radiologist members of the Society of Abdominal Radiology and urologist members of the Society of Urologic Oncology received an electronic survey regarding prostate MRI reporting. The response rate was 12% (135/1155) for Society of Abdominal Radiology and 8% (54/663) for Society of Urologic Oncology members. Most respondents in both specialties prefer Prostate Imaging Reporting and Data System version 2 (PI-RADSv2) (radiologists, 84%; urologists, 84%), indicate that it is used at their institution (radiologists, 84%; urologists, 78%), understand its implications for patient care (radiologists, 89%; urologists, 71%), and agree that radiologists apply PI-RADSv2 categories correctly (radiologists, 57%; urologists, 61%). Both specialties agreed regarding major barriers to PI-RADSv2 adoption: radiologist inexperience using PI-RADSv2 (radiologists, 51%; urologists, 51%), urologist inexperience using PI-RADSv2 (radiologists, 46%; urologists, 51%), and lack of standardized templates (radiologists, 47%; urologists, 52%). The specialties disagreed (p ≤ 0.039) regarding whether reports should include the following management recommendations: targeted biopsy (radiologists, 58%; urologists, 34%), follow-up imaging (radiologists, 46%; urologists, 28%), and time interval for follow-up imaging (radiologists, 35%; urologists, 16%). There was also disagreement (p = 0.037) regarding report style: 54% of urologists preferred fully structured reports, whereas 53% of radiologists preferred hybrid structured and free-text reports. Radiologists and urologists both strongly prefer PI-RADSv2 for prostate MRI reporting, despite recognizing barriers to its adoption. Urologists more strongly preferred a fully structured report and disagreed with radiologists' preference to include management recommendations. Collaborative radiologist-urologist educational efforts are warranted to help optimize the effect of prostate MRI reporting in patient care.